Prevention and treatment of tumor lysis syndrome, and the efficacy and role of rasburicase - Alakel, Nael (Onco Targets Ther, 2017)
Tumor lysis syndrome (TLS) is a potentially life-threatening condition that occurs in oncologic and hematologic patients with large tumor burden, either due to cytotoxic therapy or, less commonly, spontaneously because of massive tumor cell lysis. TLS is clinically characterized by acute renal failure, hyperuricemia, hyperkalemia, hyperphosphatemia, and hypocalcemia. While limited options are available for treating TLS, identifying patients at high risk for developing TLS and prevention in high-risk patients remain an important aspect in the treatment of cancer patients. In general, treatment of TLS consists of intensive hydration, stimulation of diuresis, and, more specifically, in the use of allopurinol and rasburicase. Rasburicase, a recombinant urate oxidase, rapidly and effectively reduces hyperuricemia, which subsequently significantly decreases the risk of acute renal failure and other clinical manifestations of TLS. For this review, a comprehensive literature search using the term “tumor lysis syndrome” and/or “rasburicase” was performed considering articles listed in MEDLINE. Incidence, prevention, and therapy of TLS with a special focus on the role of rasburicase are discussed. We evaluated 120 relevant articles including 35 case reports, 32 clinical trials, and 14 meta-analyses.